Rheumatoid Arthritis – Non Biologic Treatment and Small Molecules 2018
DOI: 10.1136/annrheumdis-2018-eular.6391
|View full text |Cite
|
Sign up to set email alerts
|

AB0482 Similar efficacy of tofacitinib on disease activity in rheumatoid arthritis patients with and without previous biologicals; results from the turkbio registry

Abstract: BackgroundThe aim of this study was to investigate the drug survival, its efficacy and safety in patients withRA based on the database from the Turkish TURKBIO registryMethodsA total of 180 patients were treated with TOFA forRA. Drug survival was assessed. In 118 patients with available data, treatment response was evaluated using thenumber of sensitive and swollen joints, VAS values, DAS28, HAQ and CRPat weeks 12,24,48 and 60ResultsAt baseline, RA patients had a median(Q1-Q3)disease duration of 14 years.75 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Analysis of the Swiss Clinical Quality Management in Rheumatoid Arthritis (SCQM-RA) Registry found that drug maintenance in tofacitinib initiators (n = 806) was significantly higher than TNFi initiators (n = 1862) and comparable with non-TNFi bDMARDs (eg, rituximab, tocilizumab, abatacept) initiators (n = 1355). Median (IQR) drug maintenance was 25 months (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 1.24) for both non-TNFi bDMARDs and tofacitinib. Discontinuation was most commonly due to ineffectiveness with lower rates for tofacitinib (46%) compared with non-TNFi bDMARDs (50%) and TNFi (57%).…”
Section: Effectiveness And/or Persistencementioning
confidence: 99%
“…Analysis of the Swiss Clinical Quality Management in Rheumatoid Arthritis (SCQM-RA) Registry found that drug maintenance in tofacitinib initiators (n = 806) was significantly higher than TNFi initiators (n = 1862) and comparable with non-TNFi bDMARDs (eg, rituximab, tocilizumab, abatacept) initiators (n = 1355). Median (IQR) drug maintenance was 25 months (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) 1.24) for both non-TNFi bDMARDs and tofacitinib. Discontinuation was most commonly due to ineffectiveness with lower rates for tofacitinib (46%) compared with non-TNFi bDMARDs (50%) and TNFi (57%).…”
Section: Effectiveness And/or Persistencementioning
confidence: 99%
“…Study characteristics are described in Supplementary Table 6. 28 studies were performed in patients with IA; 18,19,26-28,30-36,47,49-51,55-57, 59-63,67,79,80,83 25 in patients with RA; 7,16,17,23,24,37,39,40,[42][43][44][45]53,54,58,66,68,70,[73][74][75][76][77][78]84 5 in patients with AS; 21,25,46,48,65 4 in patients with PsA; 41,64,71,81 4 in patients with UC; 22,69,72,82 2 in patients with IBD (with results reported separately for UC); 38,52 and one in patients with SpA. 29 Most studies were retrospective (n=37), while 28 were prospective and one was cross-sectional.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Among the studies including patients with IA, 21 studies included some form of PRO, 18,20,21,23,24,27,[29][30][31]36,48,49,54,57,59,65,75,77,78,80,84 of which 10 studies reported PROs prior to the switch only and therefore did not provide any information on the patient experience of switching treatment. 20,21,23,24,[29][30][31]49,59,78 The PRO measurement tools used are summarized in Figure 3.…”
Section: Indirectly Reported Patient Experience Of Switchingmentioning
confidence: 99%
See 2 more Smart Citations